Non-occupational determinants of cadmium and lead in blood and urine among a general population in Thailand. - Jintana Sirivarasai (2018)
In this study the levels of cadmium and lead in blood and urine were measured by the method of graphite furnace atomic absorption spectrometry in 356 healthy, non-occupationally exposed individuals and the factors affecting the metal concentrations were investigated. The geometric means for cadmium in blood and urine were 0.98 microg/l (Cd-B) and 0.87 microg/gCr (Cd-U). The lead levels were 32.5 microg/l for blood (Pb-B) and 2.54 microg/gCr for urine (Pb-U). Men had significantly higher blood cadmium and lead levels than women whereas the urinary excretion rates of both metals were higher in women than men. Cigarette smoking was found to affect the levels of Cd-B, Cd-U, and Pb-B. Other factors like alcohol intake and place of residence also related to blood lead levels. Both blood and urine levels of cadmium and lead in this study group were within acceptable ranges for non-occupationally exposed populations and were decreased compared with the past. It is important to continue monitoring levels of these metals in order to prevent adverse health effects in the Thai population.